The Effect Of Gadget Usage With Digital Eye Strain (Des) In Students Of The Medical Faculty Muhammadiyah University Of Malang - Aryani Vindhya Putri; Bragastio Sidharta; Adelia Vina Larasati (Saintika Medika, 2022)
Introduction: COVID-19 pandemic have cause most people to work from home and spend more time on screens including the students of Medical Faculty Muhammadiyah University of Malang. Digital Eye Strain (DES) is a collection of symptoms such as (1). Ocular which include dry eyes, watering, eye irritation, (2). Asthenopia which includes eye fatigue, eye strain, eye pain, (3). Visuals such as double vision, difficulty changing focus, blurred vision and (4). Extraocular symptoms include back, neck and headache pain. The use of computers and digital screens for more than 3 hours will put people at risk of experiencing DES. Purpose: To determine the relationship between the duration of the use of gadgets with the complaints related to DES in the students of Faculty of Medicine, University of Muhammadiyah Malang. Result: 79 respondents with the most of age were 17-20 years old were participated in this study. There is an insignificant positive relationship between the duration on the screen and the incidence of DES (p = 0.654 > 0.05 (α = 5%)) but there is a significant positive relationship between the duration on screen and the number of symptoms experienced by students (p = 0.039 < 0.05 (α = 5%)). Keywords: Digital eye strain, computer, digital screen, covid-19, medical faculty student